PREVALENSI KELELAHAN PADA KELUARGA PASIEN DI RUANG RAWAT INAP RS IZZA CIKAMPEK DIMASA PANDEMI COVID-19 - Asma Zuinoviana; Amzal Mortin Andas; Indah Permatasari (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Fatigue in the patient's family can occur when accompanying patients who are hospitalized. This is caused by factors of quality of rest is disturbed. Overcoming fatigue can be handled by providing health information and practicing relaxation techniques, but unresolved fatigue can have an impact on emotional, economic and physical aspects, especially on health during the COVID-19 pandemic. The purpose of the study was to determine the prevalence of family fatigue in inpatient rooms during the pandemic. The design of this research is descriptive analytic with a cross sectional approach. The study population was the entire family of patients who were treated in an inpatient room during the pandemic, using an accidental sampling technique with a sample of 94 respondents. This study used a Visual Analoque Scale For Fatique (VAS –F) questionnaire. The results of the study were based on the frequency distribution of the majority who experienced mild (41.5%), moderate (36.2%) and severe (22.3%). The majority prevalence was based on age, late adulthood with mild fatigue 15 respondents, female sex with mild fatigue 21 respondents, high school/vocational education education with mild fatigue 21 respondents, working respondents with mild fatigue 23 respondents, relationship status as a child with mild fatigue 13 respondents. The conclusion shows that the majority of patients' families experience mild fatigue.